(3 intermediate revisions by 2 users not shown)
Line 1: Line 1:
<br>  
+
<center><font size= 4>
 
+
'''[[Digital_signal_processing_practice_problems_list|Practice Question on "Digital Signal Processing"]]'''
= [[:Category:Problem solving|Practice Question]], [[ECE438]] Fall 2013, [[User:Mboutin|Prof. Boutin]]  =
+
</font size>
  
On computing the inverse z-transform of a discrete-time signal.
+
Topic: Computing an inverse z-transform
  
 +
</center>
 
----
 
----
 +
==Question==
  
 
Compute the inverse z-transform of  
 
Compute the inverse z-transform of  
Line 40: Line 42:
  
 
<span class="texhtml">''x''[''n''] = ''u''[ − ''n'']( − 3<sup>''n'' − 1</sup> − 2<sup>''n'' − 1</sup>)</span>  
 
<span class="texhtml">''x''[''n''] = ''u''[ − ''n'']( − 3<sup>''n'' − 1</sup> − 2<sup>''n'' − 1</sup>)</span>  
 +
 +
:<span style="color:blue"> Grader's comment: Partial Fractions splitting is wrong </span>
  
 
=== Answer 2  ===
 
=== Answer 2  ===
Line 50: Line 54:
 
By factoring out 1/3 for the first term, and 1/2 for the second term, we can have both terms in form of <span style="color:green"> (Instructor's comment: No need to explain this.)</span>
 
By factoring out 1/3 for the first term, and 1/2 for the second term, we can have both terms in form of <span style="color:green"> (Instructor's comment: No need to explain this.)</span>
  
<math> \frac{1}{1-r} </math>, which is equal to <math> \sum_{n=0}^{+\infty} (\frac{1}{r})^n </math>  
+
<math> \frac{1}{1-r} </math>, which is equal to <math> \sum_{n=0}^{+\infty} (\frac{1}{r})^n </math> <span style="color:green"> (Instructor's comment: This is not true in general: only when |r|<1)</span>
  
 
<math>= -\frac{1}{3}(\frac{1}{1-\frac{z}{3}})-\frac{1}{2}(\frac{1}{1-\frac{z}{2}})</math>  
 
<math>= -\frac{1}{3}(\frac{1}{1-\frac{z}{3}})-\frac{1}{2}(\frac{1}{1-\frac{z}{2}})</math>  
Line 65: Line 69:
  
 
<span class="texhtml">''x''[''n''] = ''u''[ − ''n'']( − 3<sup>''n'' − 1</sup> − 2<sup>''n'' − 1</sup>)</span>  
 
<span class="texhtml">''x''[''n''] = ''u''[ − ''n'']( − 3<sup>''n'' − 1</sup> − 2<sup>''n'' − 1</sup>)</span>  
 +
 +
:<span style="color:blue"> Grader's comment: Partial Fractions splitting is wrong </span>
  
 
=== Answer 3  ===
 
=== Answer 3  ===
Line 87: Line 93:
 
now let n = -k  
 
now let n = -k  
  
<math>= -\frac{1}{3}\sum_{n=0}^{+\infty} 3^{k} z^{-k} +\frac{1}{2}\sum_{n=0}^{+\infty} 2^{k}z^{-k}</math>  
+
<math>= -\frac{1}{3}\sum_{n=0}^{+\infty} 3^{k} z^{-k} +\frac{1}{2}\sum_{n=0}^{+\infty} 2^{k}z^{-k}</math> <span style="color:green"> (Instructor's comment: Your sum is over n, but the expression depends on k.)</span>
  
 
by comparison with z-transfrom formula  
 
by comparison with z-transfrom formula  
Line 96: Line 102:
  
 
<br>  
 
<br>  
 +
 +
:<span style="color:blue"> Grader's comment: Correct Answer </span>
  
 
=== Answer 4  ===
 
=== Answer 4  ===
Line 116: Line 124:
  
 
<span class="texhtml">''x''[''n''] = ( − 3<sup>''n'' − 1</sup> − 2<sup>''n'' − 1</sup>)''u''[ − ''n'']</span>  
 
<span class="texhtml">''x''[''n''] = ( − 3<sup>''n'' − 1</sup> − 2<sup>''n'' − 1</sup>)''u''[ − ''n'']</span>  
 +
  
 
<br>  
 
<br>  
 +
 +
:<span style="color:blue"> Grader's comment: Partial Fractions splitting is wrong </span>
  
 
=== Answer 5  ===
 
=== Answer 5  ===
Line 140: Line 151:
  
 
So, x[n] = (−3<sup>n-1</sup>+2<sup>n-1</sup>)u[-n] <br>  
 
So, x[n] = (−3<sup>n-1</sup>+2<sup>n-1</sup>)u[-n] <br>  
 +
 +
:<span style="color:blue"> Grader's comment: Correct Answer </span>
 +
  
 
=== Answer 6  ===
 
=== Answer 6  ===
Line 166: Line 180:
  
 
x[n] = u[-n](2<sup>n-1</sup>-3<sup>n-1</sup>)<br>
 
x[n] = u[-n](2<sup>n-1</sup>-3<sup>n-1</sup>)<br>
 +
 +
:<span style="color:blue"> Grader's comment: Correct Answer </span>
  
 
=== Answer 7  ===
 
=== Answer 7  ===
Line 185: Line 201:
  
 
x[n] = (−3^(n−1))u[−n] - (2^(n−1))u[− n]
 
x[n] = (−3^(n−1))u[−n] - (2^(n−1))u[− n]
 +
 +
:<span style="color:blue"> Grader's comment: Partial Fractions splitting is wrong </span>
 +
  
 
[[2013 Fall ECE 438 Boutin|Back to ECE438 Fall 2013 Prof. Boutin]]  
 
[[2013 Fall ECE 438 Boutin|Back to ECE438 Fall 2013 Prof. Boutin]]  
  
 
[[Category:ECE301]] [[Category:ECE438]] [[Category:ECE438Fall2013Boutin]] [[Category:Problem_solving]] [[Category:Z-transform]] [[Category:Inverse_z-transform]]
 
[[Category:ECE301]] [[Category:ECE438]] [[Category:ECE438Fall2013Boutin]] [[Category:Problem_solving]] [[Category:Z-transform]] [[Category:Inverse_z-transform]]

Latest revision as of 12:55, 26 November 2013

Practice Question on "Digital Signal Processing"

Topic: Computing an inverse z-transform


Question

Compute the inverse z-transform of

$ X(z) =\frac{1}{(3-z)(2-z)}, \quad \text{ROC} \quad |z|<2 $.

(Write enough intermediate steps to fully justify your answer.)


Share your answers below

You will receive feedback from your instructor and TA directly on this page. Other students are welcome to comment/discuss/point out mistakes/ask questions too!


Answer 1

$ X(z) = \frac{A}{3-z}+\frac{B}{2-z} $ (Instructor's comment: You can skip this step.)

$ = -\frac{1}{3-z}-\frac{1}{2-z} $

$ = -\frac{1}{3}(\frac{1}{1-\frac{z}{3}})-\frac{1}{2}(\frac{1}{1-\frac{z}{2}}) $

$ = -\frac{1}{3}\sum_{n=0}^{+\infty} (\frac{z}{3})^n -\frac{1}{2}\sum_{n=0}^{+\infty} (\frac{z}{2})^n $

$ = \sum_{n=0}^{+\infty}[(-\frac{1}{3}) (\frac{1}{3})^n + (-\frac{1}{2})(\frac{1}{2})^n]z^n $

Let k=-n

$ = \sum_{k=-\infty}^{+\infty}u[-k][(-\frac{1}{3})3^k + (-\frac{1}{2})2^k]z^{-k} $

by comparison with z-transform formula

x[n] = u[ − n]( − 3n − 1 − 2n − 1)

Grader's comment: Partial Fractions splitting is wrong

Answer 2

Using a partial fraction expansion, we can change the original equation to

$ X(z) = \frac{A}{3-z}+\frac{B}{2-z} $ Where A = 1, B = -1, so we get (Instructor's comment: You can skip this explanation and write the expansion directly)

$ = -\frac{1}{3-z}-\frac{1}{2-z} $

By factoring out 1/3 for the first term, and 1/2 for the second term, we can have both terms in form of (Instructor's comment: No need to explain this.)

$ \frac{1}{1-r} $, which is equal to $ \sum_{n=0}^{+\infty} (\frac{1}{r})^n $ (Instructor's comment: This is not true in general: only when |r|<1)

$ = -\frac{1}{3}(\frac{1}{1-\frac{z}{3}})-\frac{1}{2}(\frac{1}{1-\frac{z}{2}}) $

$ = -\frac{1}{3}\sum_{n=0}^{+\infty} (\frac{z}{3})^n -\frac{1}{2}\sum_{n=0}^{+\infty} (\frac{z}{2})^n $

$ = \sum_{n=0}^{+\infty}[(-\frac{1}{3}) (\frac{1}{3})^n + (-\frac{1}{2})(\frac{1}{2})^n]z^n $

Then let k=-n

$ = \sum_{k=-\infty}^{+\infty}u[-k][(-\frac{1}{3})3^k + (-\frac{1}{2})2^k]z^{-k} $

Comparing it with z-transform formula, we can get

x[n] = u[ − n]( − 3n − 1 − 2n − 1)

Grader's comment: Partial Fractions splitting is wrong

Answer 3

First, using partial fraction we get..

$ X(z) = \frac{A}{3-z}+\frac{B}{2-z} $ (Instructor's comment: You can skip this step.)

A(2-z) + B(3-z) = 1

let z=2, then B=1

let z=3, then A=-1 (Instructor's comment: You do not need to explain how you got the A and the B. )

$ = -\frac{1}{3-z}+\frac{1}{2-z} $

$ = -\frac{1}{3}(\frac{1}{1-\frac{z}{3}})+\frac{1}{2}(\frac{1}{1-\frac{z}{2}}) $

$ = -\frac{1}{3}\sum_{n=0}^{+\infty} (\frac{z}{3})^n +\frac{1}{2}\sum_{n=0}^{+\infty} (\frac{z}{2})^n $

$ = -\frac{1}{3}\sum_{n=0}^{+\infty} (\frac{1}{3})^n(z)^n +\frac{1}{2}\sum_{n=0}^{+\infty} (\frac{1}{2})^n(z)^n $

now let n = -k

$ = -\frac{1}{3}\sum_{n=0}^{+\infty} 3^{k} z^{-k} +\frac{1}{2}\sum_{n=0}^{+\infty} 2^{k}z^{-k} $ (Instructor's comment: Your sum is over n, but the expression depends on k.)

by comparison with z-transfrom formula

x[n] = − 3n − 1u[ − n] + 2n − 1u[ − n]

x[n] = ( − 3n − 1 + 2n − 1)u[ − n]


Grader's comment: Correct Answer

Answer 4

$ X(z) = \frac{A}{3-z}+\frac{B}{2-z} $ (Instructor's comment: You can skip this step.)

$ = -\frac{1}{3-z} - \frac{1}{2-z} $

$ = -\frac{1}{3}(\frac{1}{1-\frac{z}{3}})-\frac{1}{2}(\frac{1}{1-\frac{z}{2}}) $

$ = -\frac{1}{3}\sum_{k=0}^{+\infty} (\frac{z}{3})^k -\frac{1}{2}\sum_{k=0}^{+\infty} (\frac{z}{2})^k $

$ = \sum_{k=0}^{+\infty}[(-\frac{1}{3})(\frac{1}{3})^k + (-\frac{1}{2})(\frac{1}{2})^k]u[k] * z^k $

Substitute k with -n

$ = \sum_{n=-\infty}^{+\infty}[(-\frac{1}{3})3^{-n} + (-\frac{1}{2})2^{-n}]u[-n] * z^{-n} $

Look up Z transform equation on RHEA table and see that X(z) becomes...

x[n] = ( − 3n − 1 − 2n − 1)u[ − n]



Grader's comment: Partial Fractions splitting is wrong

Answer 5

by partical fraction, we get,

$ X(z) = \frac{A}{3-z}+\frac{B}{2-z} $ (Instructor's comment: You can skip this step.)

$ = -\frac{1}{3-z}+\frac{1}{2-z} $

For $ \quad \text{ROC} \quad |z|<2 $

$ X(z)= -\frac{1}{3}(\frac{1}{1-\frac{z}{3}})+\frac{1}{2}(\frac{1}{1-\frac{z}{2}}) $


$ = -\frac{1}{3}\sum_{n=0}^{+\infty} (\frac{z}{3})^n +\frac{1}{2}\sum_{n=0}^{+\infty} (\frac{z}{2})^n $

assume n=-k.

$ X(z)= -\frac{1}{3}\sum_{k=-\infty}^{0} 3^{k} z^{-k} +\frac{1}{2}\sum_{k=-\infty}^{0} 2^{k}z^{-k} $


$ = \sum_{k=-\infty}^{+\infty}u[-k][(-\frac{1}{3})3^k + \frac{1}{2}2^k]z^{-k} $

So, x[n] = (−3n-1+2n-1)u[-n]

Grader's comment: Correct Answer


Answer 6

$ X(z) = \frac{A}{3-z}+\frac{B}{2-z} $ (Instructor's comment: You can skip this step.)

$ = \frac{1}{2-z}-\frac{1}{3-z} $

$ = \frac{1}{2}\frac{1}{1-\frac{z}{2}}-\frac{1}{3}\frac{1}{1-\frac{z}{3}} $

By the geometric series formula,

$ X(z) = \frac{1}{2}\sum_{n=0}^{+\infty}(\frac{z}{2})^n - \frac{1}{3}\sum_{n=0}^{+\infty}(\frac{z}{3})^n $

$ = \sum_{n=0}^{+\infty}(\frac{1}{2}(\frac{1}{2})^n - \frac{1}{3}(\frac{1}{3})^n)z^n $

$ = \sum_{n=-\infty}^{+\infty}u[n]((\frac{1}{2})^{n+1} - (\frac{1}{3})^{n+1})z^n $

Substituting k = -n for n gives,

$ X(z) = \sum_{k=-\infty}^{+\infty}u[-k](\frac{1}{2}^{-k+1} - \frac{1}{3}^{k+1})z^{-k} $

$ = \sum_{k=-\infty}^{+\infty}u[-k](2^{k-1} - 3^{k-1})z^{-k} $

By comparison with the Z-transform formula,

x[n] = u[-n](2n-1-3n-1)

Grader's comment: Correct Answer

Answer 7

$ X(z) =\frac{1}{(3-z)(2-z)} $

$ = \frac{A}{3-z}+\frac{B}{2-z} $ (Instructor's comment: You can skip this step.) $ = -\frac{1}{3-z}-\frac{1}{2-z} $

$ = -\frac{1}{3}*(\frac{1}{1-\frac{z}{3}})-\frac{1}{2}*(\frac{1}{1-\frac{z}{2}}) $ (Instructor's comment: Be careful! You do not mean convolution here, do you? Then you should use $ \times $ instead of $ * $.)

$ = -\frac{1}{3}\sum_{n=0}^{+\infty}(\frac{z}{3})^n -\frac{1}{2}\sum_{n=0}^{+\infty}(\frac{z}{2})^n $ $ = -\frac{1}{3}\sum_{n=0}^{+\infty}(\frac{1}{3})^n(z)^n -\frac{1}{2}\sum_{n=0}^{+\infty}(\frac{1}{2})^n(z)^n $

substituting k for -n:

$ = -\frac{1}{3}\sum_{n=0}^{+\infty}3^{k} z^{-k}-\frac{1}{2}\sum_{n=0}^{+\infty}2^{k}z^{-k} $

Using the Z transform tables to find the common transformation: (Instructor's comment: I don't understand what you mean. You should rephrase this.)

x[n] = (−3^(n−1))u[−n] - (2^(n−1))u[− n]

Grader's comment: Partial Fractions splitting is wrong


Back to ECE438 Fall 2013 Prof. Boutin

Alumni Liaison

Sees the importance of signal filtering in medical imaging

Dhruv Lamba, BSEE2010